Basal cell hyperplasia of prostate - an entity a urologist must know - Suresh Bhat; Appu Thomas; M Nazar; George C Joseph; Dharmaraj (Indian Journal of Urology, 2000)
We report 2 cases of basal cell hyperplasia of prostate, which is an uncommon and elusive lesion. It is commonly associated with benign prostatic hyperplasia (BPH) and may sometimes be mistaken for malignancy. The know-ledge about this disease helps in the correct diagnosis and avoidance of unnecessary or overtreatment.